Effect of stabilisation on mechanical properties, moisture buffering and water durability of hypercompacted earth. (15th September 2017) - Bruno, Agostino Walter; Gallipoli, Domenico; Perlot, Céline; Mendes, Joao
Highlights: Stabilisation affects hygroscopic and mechanical behaviour of hypercompacted earth. Alkaline activation and silicone-based admixture are adopted to stabilise earth. Strength, stiffness, moisture buffering and water durability are investigated. Stabilisation improves durability but reduce strength, stiffness and moisture buffering. Abstract: This paper investigates the effect of stabilisation by alkaline activation and silicon based admixture on the mechanical properties, moisture buffering capacity and durability of an earthen material for building construction. The stiffness and strength of both unstabilised and stabilised cylindrical samples were measured, under different humidity conditions, by means of unconfined compression tests. The effect of stabilisation on moisture buffering capacity was instead explored by subjecting samples to cyclic variations of relative humidity at constant temperature, according to the experimental procedures prescribed by the norm ISO 24353 [21]. Finally, durability against water erosion was assessed by performing immersion, suction and liquid contact tests on both unstabilised and stabilised samples according to the norm DIN 18945 [16]. Results from this extensive experimental campaign highlighted that the chosen stabilisation methods improved the durability of the material while maintaining a relatively good mechanical performance and a good to excellent moisture buffering capacity.